Individual Responses to Repeated Dosing with Anthocyanin-Rich New Zealand Blackcurrant Extract During High-Intensity Intermittent Treadmill Running in Active Males - Perkins, Ian C.; Blacker, Sam D.; Willems, Mark E. T. (Nutrients, 2024)
Intake of New Zealand blackcurrant (NZBC) extract for 7 days has been shown to improve high-intensity intermittent running (HIIR) performance. Objectives: We examined the repeat response of NZBC extract on HIIR performance. Methods: Sixteen active males (age: 23 ± 3 yrs, height: 179 ± 5 cm, mass: 79 ± 11 kg, V˙O2max: 55.3 ± 5 mL∙kg−1∙min−1, velocity at V˙O2max: 17.2 ± 0.8 km∙h−1, mean ± SD) participated. Familiarized subjects completed the HIIR test at individualized exercise intensities with stages consisting of six 19 s high-intensity running bouts interspersed by 15 s of low-intensity running and 1 min of inter-stage rest. The test was repeated at increasing speeds until exhaustion, under four conditions; two with a daily dose of 600 mg of NZBC extract (CurraNZ™, providing 210 mg anthocyanins) and two with a placebo, each over 7 days. The study used a double-blind, randomized, cross-over design with a wash-out period of at least 14 days. Results: For the cohort, there were no differences between the placebo and NZBC conditions for mean heart rate (p = 0.071), mean oxygen uptake (p = 0.713), and mean lactate (p = 0.121) at exhaustion for the HIIR. The NZBC extract increased the mean total running distance and mean high-intensity running distance by 7.9% and 8.0% compared to the placebo. With NZBC extract, 8 of the 16 participants (50%) enhanced in both trials beyond the smallest worthwhile change for total running distance (≥173 m) and high-intensity running distance (≥111 m). For repeated responders, total running distance and high-intensity running distance was increased by 16.7% (95% CI [11.0, 22.4%] and 16.6% (95% CI [11.0, 22.2%]. Three participants had enhanced running performance in one trial beyond the SWC, and five participants were considered non-responders. Conclusions: This is the first study on the repeated response by an anthocyanin-rich supplement on high-intensity running performance. New Zealand blackcurrant extract can substantially enhance intermittent high-intensity running performance in consistent responders. Future work should examine dosing strategies of New Zealand blackcurrant, and whether a repeated response rate exceeding 50% can be attained. These findings suggest that NZBC extract could be beneficial for athletes participating in high-intensity team sports.